Board size and accounting conservatism of Malaysian listed firms - Abdul Manaf, Kamarul Bahrain; Amran, Noor Afza; Zainol Abidin, Azlan (INSInet Publications, 2014)
Board of directors is entrusted with responsibilities to monitor operations of firms. Therefore, the board should have effective characteristics to ensure the interest of shareholders is protected.In view of that, Code of Corporate Governance was issued in Malaysia in 2000 to strengthen the board.Objective: This paper examines board size, one of the board’s characteristics, to assess whether it is big or small board that produces high quality financial reporting.In particular, it examines the effect of board size on the level of accounting conservatism for Malaysian firms listed on Bursa Malaysia. Accounting conservatism is an important element in good quality financial reporting Sample of this study consists of 3,852 firm-year observations of non-financial firms over the period 2001-2012. Results: From the analysis, results reveal that the level of accounting conservatism is higher for firms with small board size.Conclusion: With respect to financial reporting quality, board of directors is more effective when the number of board members is small